Applications of synthetic microbial communities platform through plant growth-promoting traits to enhance ecological functions in sustainable agriculture - Chanchao Chem; Sreyneang Nhim; Thev Pol; Sreylen Meas; Eneang Ourn; Techchheng San; Channa Nget; Tsukasa Ito (Universitas Sebelas Maret, 2025)
Synthetic microbial communities (SynCom) present a promising strategy for sustainably enhancing agricultural productivity and ecological resilience. This review critically discusses recent advancements in applying SynCom within agricultural ecosystems and highlights their practical benefits for economic sustainability. Plant growth-promoting (PGP) traits are essential for developing SynCom, as they enhance plant growth, increase nutrient uptake, improve stress tolerance, and support resistance to pathogens. SynCom demonstrates significant effectiveness as a biofertilizer, substantially improving soil health and crop yields through enhanced nutrient cycling and bioavailability. Its role as a biopesticide is also significant, as it offers an eco-friendly approach to insect pest management. The integration of SynCom into agricultural practices has proven to enhance plant disease resistance, significantly contributing to crop resilience. Moreover, SynCom plays a vital role in maintaining soil fertility, promoting carbon sequestration, and mitigating the impacts of climate change. Its applications extend to environmental remediation, where it effectively degrades hazardous pollutants in agricultural soils and efficiently processes lignocellulosic biomass, supporting sustainable biomass utilization. SynCom offers considerable advantages but also faces challenges, including community stability, environmental adaptability, and regulatory concerns. Future research efforts aim to address these limitations and enhance SynCom's efficacy regarding long-term agricultural sustainability. Our review provides valuable insights for policymakers, practitioners, and researchers to construct SynCom-based strategies that promote plant growth, enhance sustainable agriculture, and support environmental conservation.